Institutional finance for agricultural development: an analytical survey of critical issues - Desai, Bhupat M.; Mellor, John W. (International Food Policy Research Institute, 1993)
In reviewing the literature for Institutional Finance for Agricultural Development: An Analytical Survey of Critical Issues, Bhupat M. Desai and John W. Mellor look at how rural financial institutions (RFIs) are organized, how they can improve their financial viability, and how real interest rates affect the demand for rural loans, the supply of rural deposits, and rural savings. Their purpose is to make the findings of the extensive literature on agricultural credit policy accessible to developing-country policymakers.